Diagnosis and treatment of vulval disease - Sobstyl, Małgorzata; Tkaczuk-Włach, Joanna; Tarkowski, Rafał; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
Symptoms of vulval disease are not characteristic. Women with this disease complain of pruritus, pain, changes of the color and structure of vulva’s skin. Diagnosis can be difficult to determine because changes may be affected by immunological reactions and lack of estrogens in post menopausal women. A comprehensive differential diagnosis should include: vulvitis, lichen sclerosus, lichen planus, vulval intraepithelial neoplasia (VIN) and rare diseases: Behçet’s disease, Zoon vulvitis and extramammary Paget’s disease.